2013
DOI: 10.1021/ef4000825
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for Inhibition of Asphaltenes Damage: Adsorption Study and Displacement Test on Porous Media

Abstract: The deposition of asphaltenes is one of the most difficult problems to overcome in oil production and processing. The presence of asphaltenes in crude oil, and consequently, the adsorption and deposition of asphaltenes on the rock surfaces, affects the rock properties, such as porosity, permeability, and wettability. This study aims at analyzing the effect of the chemical nature of 12 types of nanoparticles on asphaltenes adsorption; hence, the delay or inhibition of deposition and precipitation of asphaltenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
161
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(171 citation statements)
references
References 48 publications
8
161
1
1
Order By: Relevance
“…Most of the previous studies showed that the nanoparticles are good choices for adsorption and catalytic oxidation of asphaltene in crude oil upgrading process [11,13,19] while, limited researches have been carried out on using nanoparticles in porous media for asphaltene adsorption and consequently reduction of asphaltene deposition through oil flooding [17,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies showed that the nanoparticles are good choices for adsorption and catalytic oxidation of asphaltene in crude oil upgrading process [11,13,19] while, limited researches have been carried out on using nanoparticles in porous media for asphaltene adsorption and consequently reduction of asphaltene deposition through oil flooding [17,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Then, at the pressure of 5,400 psi which is close to the oil's bubble point pressure, core injection was attempted under three altered flow-rate conditions of 6, 9, and 18 (cc/h). The asphaltene content of the oil was determined based upon the IP 143 (ASTM D6560) standard method (Energy Institute 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies focusing on NiO nanoparticles (Abu Tarboush and Husein 2012a, b) explored the remarkable affinity characteristics of NiO nanoparticles toward adsorption of asphaltenes, which indeed served as our main motivation for its choice in the present work. More recently, Franco et al (2013) studied the effects of different types of nanoparticles for causing delay or inhibition in asphaltene deposition in porous media under flow conditions. The experiments unveiled the good property of the considered nanoparticles in having relatively short adsorption equilibrium time for asphaltene (*2 min), which implies promising potential of delaying agglomeration and inhibition of asphaltene precipitation in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Similar behavior was also observed in the presence of the diverse nanoparticles (Al 2 O 3 , SiO 2 and SiO 2 A) tested, however, a lower d asp and faster stabilization (180 min) was attained in a decreasing order of SiO 2 A < SiO 2 <Al 2 O 3 . Franco et al [73] conducted an asphaltene displacement and adsorption test to inhibit formation damage using nanoparticles at reservoir conditions. The authors reported a significant increase in oil production level owing to the presence of nanoparticles.…”
Section: Asphaltene Growth Inhibitionmentioning
confidence: 99%